A longitudinal study of migration propensities for mixed ethnic unions in England and Wales - Zhiqiang Feng; Maarten van Ham; Paul Boyle; Gillian M. Raab (Institute for the Study of Labor (IZA), 2012)
Most studies investigating residential segregation of ethnic minorities ignore the fact that the majority of adults live in couples. In recent years there has been a growth in the number of mixed ethnic unions that involve a minority member and a white member. To our knowledge, hardly any research has been undertaken to explicitly examine whether the ethnic mix within households has an impact on the residential choices of households in terms of the ethnic mix of destination neighbourhoods. Our study addresses this research gap and examines the tendencies of migration among mixed ethnic unions in comparison with their co-ethnic peers. We used data from the Longitudinal Study for England and Wales. Our statistical analysis supports the spatial assimilation theory: ethnic minorities move towards less deprived areas and to a lesser extent also towards less ethnically concentrated areas. However, the types of destination neighbourhood of minority people living in mixed ethnic unions varied greatly with the ethnicity of the ethnic minority partner.
urn:nbn:de:101:1-201206146714
Keywords: J12; J15; J61; R23; 330; mixed ethnic unions; migration; deprivation; ethnic concentration; longitudinal analysis; Ethnische Gruppe; Wohnstandortwahl; Ehe; Ethnische Beziehungen; Migranten; Bevölkerung; Großbritannien